Большая книга ужасов 63: [повести] / Елена Арсеньева - Арсеньева Елена Арсеньевна (Большая книга ужасов, 2015)
Экземпляры: ф.19 (20151226) / Инвентарный номер: 52515 / Цена: 217.00. / Сис.шифр: Р2 / Авт.знак: А 85 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4